Do Economic Factors Dominate Happiness: A Comparison of Western and Eastern Cultures - Nusantara, Agung; Nawatmi, Sri (Untag Business and Accounting Review, 2023)
This article explores the factors influencing happiness levels and compares them within the contexts of Western and Eastern cultures. It particularly examines the role of income in shaping happiness, with a focus on Western cultures, often associated with materialism, and Eastern cultures, frequently linked to spirituality. The analysis reveals four significant determinants of happiness: economic achievement, social support, health, and the freedom to make choices. While income, measured by per capita GDP growth, contributes to happiness, globally, freedom of choice and social support exert a more substantial influence. This holds true when comparing Europe and North America to Asia (excluding the Middle East) and when contrasting Western and Eastern cultures. The study underscores the significance of social and political factors in achieving happiness, emphasizing the need for prioritizing their development. Furthermore, it challenges the notion that Western cultures are solely materialistic and Eastern cultures entirely spiritual, highlighting the intricacies of cultural differences. In sum, these findings emphasize the need for more comprehensive and diverse research to understand variations within specific cultural and ethnic contexts.